The Influence Of Emotional Intelligence, Social Support And Competency On Lecturer Performance Mediated By Job Stress - Surya, Putu Pryanka Chitta; Sanica, I Gede (International Journal of Economics Development Research (IJEDR), 2024)
Bali Institute of Technology and Health (ITEKES) is one of the technology and health colleges in Bali that focuses on providing affordable education to all levels of society, from low to middle economy, regardless of social status or ability. The purpose of this study is to determine the Effect of Emotional Intelligence, Social Support and Competence on Lecturer Performance Mediated by Work Stress. The type of data used in this study is quantitative data. The number of samples used in this study was 87 people. Data were collected by distributing questionnaires via Google form with an interval scale of 1-10. Data analysis using the Equition Modeling structure was carried out using the Part Lease Square approach. The results of this study indicate that emotional intelligence, work support, ability have a negative effect on work stress and emotional intelligence, social support, competence have a positive effect and are mediated by work stress